Develop and Implementation of Solar Powered Ventilation System - Hairol Nizam Mohd Shah; Zalina Kamis; Mohd Fairus Abdollah; Mohd Khairi Mohd Zambri; Faizil Wasbari; Nursabillilah Mohd Ali; Amirul Anwar Mat Shah (Institute of Advanced Engineering and Science, 2018)
A ventilation system comprising a ventilator or fan to inhale fresh air from environment surrounding enters the cabin of a car where at the same time exhale the hot air to the outside. This invention system is using solar power integrate with the ventilation system in order to stabilize the thermal condition inside the car during sunny day. The solar power is chosen as it is reasonable due to its limitless and environmental friendly source just like mentioned in the previous objective of the project. In addition, a rechargeable battery is used to power the ventilator in the absence of the alternative energy during cloudy day or has obstacle like being shaded by buildings, trees and others. It is just like an extra supply during emergency case. This may prevent the lack of power energy supply for the system. A heat sensor is used as to detect targeted (high temperature) and desired temperature (drop temperature) inside the car. It is operatively connected to a logic circuit to measure environmental factor, wherein the controller (PIC Microcontroller) utilizes the measured environmental condition to allow the power supply to activate or deactivate the ventilator.